Interference effects of radical markings and stroke order animations on Chinese character learning among L2 learners - Hou, Fengyun; Jiang, Xin (Frontiers in Psychology, 2022)
There is controversy around whether presenting sub-character units such as radicals and strokes are beneficial to L2 Chinese learning. The present study explored the effects of radical markings (i.e., marked radicals with different colors) and stroke order animations on learning Chinese characters. Forty Chinese L2 learners with native alphabetic languages were divided into high- and low-level groups. They were first required to learn Chinese characters under four conditions either: a) presented radical markings with stroke animations; b) presented no radical markings with stroke animations; c) presented radical markings without stroke animations; or d) presented neither radical markings nor stroke animations. After learning, the participants were given character recognition and character-meaning matching tests. Results showed that the presentation of radical markings increased the participants’ reaction times in the character recognition test and decreased their recognition accuracy. Moreover, presenting stroke order animations also decreased the participants’ accuracy in recognizing characters. Beyond that, presenting radical markings and stroke order animations had no significant influence on character-meaning matching tests. These results indicate that providing radical and stroke information might interfere with character learning instead of facilitating character learning. The findings contribute to theoretical arguments about the analytic and holistic processing of Chinese characters and the pedagogical implications for teaching Chinese as a second language.